Qualitative understandings of the persistent use of traditional contraceptive methods using the socio-ecological model among older reproductive-age women in Khulna, Bangladesh - Mashiat Abedin; Mohammad Bellal Hossain (PLoS ONE, 2025)
Background The continued use of Traditional Contraceptive Methods (TCM) among Bangladeshi women of reproductive age (aged 35–49 years) poses a significant public health issue. Existing research in Bangladesh suggests that women in this age group use TCM more than their younger counterparts. However, the reason for the higher TCM use among Bangladeshi women of reproductive age is yet to be explored—the current study aimed to understand the use of TCM among Bangladeshi women aged 35 years. Methods This qualitative study employed purposive sampling from the Khulna district to conduct ten in-depth interviews with women aged 35–49 years and seven key informant interviews with family planning service providers. A socio-ecological model was adopted for this study. Data were collected in January 2024. The interviews were audio-recorded and transcribed verbatim. Thematic data analysis was performed. Results At the individual level, women’s poor knowledge and fear of the side effects of modern contraceptive methods, perceptions related to the effectiveness, risks, and benefits, ease of use, and cost shaped the use of TCM. Interpersonal factors included the influence of spouses, mothers-in-law, and peer groups on the women. Community norms and beliefs are also pivotal in this regard. Institutional factors include providers’ attitudes, health facility-related issues such as distance from the house, waiting in queues, unavailability of products, and policy-level influences, such as the lack of an updated policy that promotes TCM use among older women of reproductive age in Bangladesh. Conclusion The complex interplay of various factors shapes the use of TCM in Bangladesh. Therefore, comprehensive reproductive health education programs should be considered to enable women to make informed choices about contraceptive use and switch from traditional to modern contraceptive methods, such as long-acting methods. This will ultimately lead to improved reproductive health outcomes.